2000
DOI: 10.1029/1999jd901047
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of cold‐season processes in the MAPS land‐surface scheme

Abstract: Abstract. A coupled atmospheric/land-surface model covering the conterminous UnitedStates with an associated 1-hour atmospheric data assimilation cycle, the Mesoscale Analysis and Prediction System (MAPS), has been improved to include a snow accumulation/melting scheme and also parameterization of processes in frozen soil. The new aspects of the land-surface model are described in this paper, along with detailed one-dimensional (l-D) tests using an 18-year observation data set from Valday, Russia. These tests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
147
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(148 citation statements)
references
References 15 publications
0
147
0
1
Order By: Relevance
“…The modelling incorporated the following: for convection, the KF (Kain, 2004), BMJ (Betts and Miller, 1986;Janjić, 2000), GDE (Grell and Dévényi, 2002) and Grell-2 (NG: New Grell) schemes; for PBL the Yonsei University (YSU; Hong et al, 2006), MYJ (Mellor and Yamada, 1982;Janjić, 2002) and Asymmetrical Convective Model version 2 (ACM; Pleim, 2007) schemes; for cloud microphysics the LIN (Lin et al, 1983), WRF single moment 3-class (WSM3; Hong et al, 2004) and WRF Single moment 6-class (WSM6; Dudhia et al, 2008) schemes; and for surface processes the five-layer soil thermal diffusion model (SOIL; Dudhia, 1996), the NOAH land surface model (Chen and Dudhia, 2001) and rapid update cycle model (RUC; Smirnova et al, 2000). As mentioned earlier, a total of 13 simulations were conducted for each of the five TCs, with a sequential order of (i) cumulus convection, (ii) microphysics, (iii) PBL turbulence and (iv) land-surface physics, such that the best CC scheme is identified first, followed by CMP sensitivity experiments with only the best CC in order to identify the best CMP scheme; the selected CC and CMP schemes are then used for three PBL sensitivity experiments, followed by surface processes sensitivity experiments with the selected CC, CMP and PBL schemes.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…The modelling incorporated the following: for convection, the KF (Kain, 2004), BMJ (Betts and Miller, 1986;Janjić, 2000), GDE (Grell and Dévényi, 2002) and Grell-2 (NG: New Grell) schemes; for PBL the Yonsei University (YSU; Hong et al, 2006), MYJ (Mellor and Yamada, 1982;Janjić, 2002) and Asymmetrical Convective Model version 2 (ACM; Pleim, 2007) schemes; for cloud microphysics the LIN (Lin et al, 1983), WRF single moment 3-class (WSM3; Hong et al, 2004) and WRF Single moment 6-class (WSM6; Dudhia et al, 2008) schemes; and for surface processes the five-layer soil thermal diffusion model (SOIL; Dudhia, 1996), the NOAH land surface model (Chen and Dudhia, 2001) and rapid update cycle model (RUC; Smirnova et al, 2000). As mentioned earlier, a total of 13 simulations were conducted for each of the five TCs, with a sequential order of (i) cumulus convection, (ii) microphysics, (iii) PBL turbulence and (iv) land-surface physics, such that the best CC scheme is identified first, followed by CMP sensitivity experiments with only the best CC in order to identify the best CMP scheme; the selected CC and CMP schemes are then used for three PBL sensitivity experiments, followed by surface processes sensitivity experiments with the selected CC, CMP and PBL schemes.…”
Section: Numerical Experimentsmentioning
confidence: 99%
“…Viterbo et al, 1999;Smirnova et al, 2000). For example, comparisons of results from the Project for Intercomparison of Land Surface Parameterization Schemes have shown that the models with an explicit frozen soil scheme provide more realistic soil temperature simulation during winter than those without (Luo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Special feature of RUC LSM is a thin layer spanning the ground surface that includes half of the first atmospheric layer and half of the top soil layer is used to solve the energy budgets. The heat storage in the layer is determined by contribution of soil fluxes and atmospheric fluxes (Smirnova et al, 1997). In RUC LSM, the latent heat flux is directly affected by vegetation through incorporation of free water from canopy and evapotranspiration.…”
Section: Land Surface Schemesmentioning
confidence: 99%
“…The model solves heat diffusion, Richards diffusive and gravitational motions for soil moisture transfer (Richards, 1931). In the cold season phase changes of soil moisture are considered (Smirnova et al, 1997). Special feature of RUC LSM is a thin layer spanning the ground surface that includes half of the first atmospheric layer and half of the top soil layer is used to solve the energy budgets.…”
Section: Land Surface Schemesmentioning
confidence: 99%
See 1 more Smart Citation